Dutton's introduction to physical therapy and patient skills - Dutton, Mark (New York McGraw Hill, 2021)
Introduction to Physical Therapy and Patient Skills, Second Edition is intended to provide updates foundation upon which to improve an individuals foundation in the challenging yet rewarding field of physical therapy. Written by a practicing physical therapist, this comprehensive textbook provides conceptual framework necessary to understand every aspect of physical therapy and eventually perform physical therapy intervention"--
The Profession -- Healthcare Policy -- Evidence-Informed Practice -- Foundations of Movement -- Patient/Client Management -- Movement Dysfunction -- Correcting Movement Dysfunction -- Preparation for Patient Care -- Monitoring Vital Signs -- Bed Mobility, Patient Positioning, and Draping -- Range of Motion -- Manual Muscle Testing -- Patient Transfers and Mobility -- Gait Training.
Preceded by Introduction to physical therapy and patient skills / by Mark Dutton. [2014]
Includes bibliographical references and index.
Keywords: Physical Therapy Specialty; Physical Therapists; Physical Therapy Modalities